Rodomonte and Corsamonte must die. Heroicity, death and story endings in the mid-sixteenth Century (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2021)
The essay investigates the relationship between the notion of Hero, Death and the End of the Story in the difficult transition from chivalric romance to heroic poem in the mid-sixteenth century. In particular, the decisive duels of Ludovico Ariosto’s Orlando Furioso and of Gian Giorgio Trissino’s Italia liberata dai Goti are investigated and compared, in order to highlight the continuity and discontinuity elements. The two poems represent two opposite but interdependent poles of this transition from chivalric romance to heroic poem. In the duels between Ruggiero and Rodomonte, and in the battle on Lipadusa (in Ariosto’s poem), and in the Corsamonte’s venture and in the final clash (in Trissino’s poem), a new and modern heroic model takes shape through the dialectic between epos and chivalric romance.
Keywords: Ariosto; Orlando furioso; Trissino; Italia liberata dai Goti; Rodomonte; Ruggiero; Epic; Romance; Duel; End of th Story; Battle of Lipadusa; Corsamonte